Effects of Fe doping on the photoelectrochemical properties of CuO photoelectrodes. (15th April 2019) - Oh, Jaejin; Ryu, Hyukhyun; Lee, Won-Jae
Abstract: In this study, CuO photoelectrodes doped with various iron concentrations were grown by using a modified chemical bath deposition method. We investigated the effects of the iron doping concentration on the morphological, structural, optical, electrical and photoelectrochemical properties of the CuO photoelectrode by using field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), UV-visible spectrophotometry (UV-Vis), electrochemical impedance spectroscopy (EIS) and potentiostatic/galvanostatic analysis, respectively. In this study, the smallest dislocation density, highest charge carrier density and lowest charge transfer resistance values were obtained from the sample with an Fe doping concentration of 2 at%. As a result, the maximum photocurrent density value of −1.44 mA/cm 2 was obtained at −0.55 V (vs. SCE) from the photoelectrode with an Fe doping concentration of 2 at%, which was 53% higher than that of the undoped CuO photoelectrode.